Academic versus Vocational Orientation: A Comparison of Guidance and Counseling Program Management in Senior High Schools and Vocational High Schools (Literature Study) - Resty Tri Mahanani (Journal of Golden Generation Education, 2025)
Rooted in the differences in educational orientation between senior high schools (academic) and vocational high schools (vocational), there is a need for different approaches to guidance and counseling (BK) management. A systematic literature review was conducted to analyze the differences in the implementation of BK management in senior high schools and vocational high schools and to formulate a more responsive management model. The results of the study show that even though the same management framework (planning, organizing, acting, controlling) is used, the implementation of BK management at both levels of education is still not fully adaptive to the characteristics of each orientation. The most significant gap lies in the functions of evaluation and accountability. At the high school level, although the evaluation process is often simple and focuses on administrative output, this practice is still considered to be in line with its academic orientation. However, at the vocational school level, the evaluation function is not only technically weak but also irrelevant to the vocational orientation. This condition shows that BK management in Indonesia needs to be strengthened so that it is truly adaptive to the academic needs of high school students and the vocational needs of vocational school students.